Exploring the evolutionary journey of the lumpy skin disease virus through the phylogenetic and phylo-geo network analysis - Bayyappa, Manjunatha Reddy Gundallahalli; Pyatla, Manoj Kumar Goud; Pabbineedi, Sai Mounica; Gunturu, Narasimha Tanuj; Peela, Sai Manohar; Nagaraj, Sudeep; Tadakod, Sunil; Gandham, Ravi Kumar; Gulati, Baldev Raj (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionLumpy Skin Disease Virus (LSDV), an emerging pathogen from the Capripoxvirus genus, continues to challenge global livestock health with its expanding host range and genetic adaptability.Materials and methodsIn this study, we report the first isolation and whole genome sequencing of LSDV from Bos frontalis, a semi-domesticated bovine species native to Northeast India, along with the assembly of an isolate from cattle.ResultsTime to the Most Recent Common Ancestor (TMRCA) estimates support a relatively recent common origin for Indian strains, pointing to ongoing virus circulation and regional adaptation. The maximum likelihood phylogenetic tree of the whole genome and G protein-coupled chemokine receptor (GPCR) gene further demonstrated the clustering of global strains, emphasizing the virus’s transboundary movement and genomic diversity. To strengthen phylogenetic inference, we identified shared SNPs, synonymous and non-synonymous mutations across the genome with a total of 2212 variants. Haplotype network and mutation pattern analyses across global genomes further highlighted the conservative evolution of Indian isolates within a distinct haplogroup.DiscussionSeveral mutation events between haplogroups highlight the virus’s continuous genetic diversification, which correlates with known patterns of spread.